Kulturna dediščina Majev - Terčelj, Marija Mojca (Etnolog. Nova vrsta (Ljubljana), 2015)
The right of indigenous peoples to unrestricted access and co-management of their own cultural heritage was officially declared already in 1989, by Convention No. 169 of the International Labour Organisation on the rights of indigenous peoples and tribal communities. This convention indeed lays down the rights of indigenous peoples to land, traditions, language, and all other human rights without discrimination. The convention requires that the representatives of indigenous peoples are consulted on issues that affect them, and together with the Declaration of the United Nations on the rights of indigenous peoples from 2006 represents the principal international standard for the protection of indigenous cultures. The problem lies in who defines what cultural heritage is, and who is responsible for its protection. Referring to the case of the pre-colonial archaeological monuments of Yucatan, which have been entered in the World Heritage List, the article describes the discrepancies between the official cultural strategy and practice and the demands of the surviving local communities.
Keywords: kulturna dediščina; cultural heritage; indigenous people; staroselci; identiteta; identity; Maji; Maya; Mayan Civilization; Mehika; Mexico